Mangrove vulnerability model of Langkawi using geospatial method / Nurhafizha Nordin - Nordin, Nurhafizha (2022)
A mangrove is a type of woody tree or shrub that grows along sheltered coasts in tropical or subtropical climates. The many species of mangroves aren't strictly linked to one another, but they do have the remarkable capacity to flourish in salty soil within reach of the tides. To achieve this goal, the study recommends examining natural and human impacts on channel morphological changes, followed by an get the risk ranking of the Mangrove Vulnerability index (MVI) and producing the final map of MVI by using the geospatial method. The findings of mangrove species, mangrove diameter, mean tidal range and human activity were used to evaluate the MVI. As the result, four parameters have been selected in this study and classified into five vulnerability raking: very low, low, moderate, high, and very high. A thorough MVI was produced by integrating the differential weighted rank values of the variables. The most risk ranking is human activities in high vulnerability level and follow by mangrove diameter in low vulnerability and in very low vulnerability is mangrove species and mean tidal range. The result in MVI is 1.414 for the MVI value and 50% for the percentile of MVI. The final MVI map produced for this study is a consequence of combining all the characteristics, and the Tuba Island region classified moderately vulnerable. Finally, the outcome of this study is to model the vulnerability of the mangrove channel to promote more sustainable exploration and use of the Tuba Island channel soon.